Yakubchak A. V. The first poetical collection of Dmitriy Klenovskiy - Yakubchak A. V. (Philological Treatises, 2020)
The first poetical collection of D.Klenovskiy “Palitra”is characterized in the article. It was considered to be lost and was unknown among the researchers. The book came out in 1917 and in terms of the revolution it didn't become the fact of the literary process. The author gives the description of the book , makes the brief analysis of the contents for the first time and concludes that D.Klenovskijy appears as a typical follower of the aesthetics of acmeists and the poetical traditions of the “silver age”.